THE EFFECT OF PERORAL POLYVINYL CHLORIDE MICROPLASTIC ON ALKALINE PHOSPHATASE AND GAMMA-GLUTAMYL TRANSFERASE LEVELS IN RATTUS NORVEGICUS WISTAR STRAIN - Leonardo S Wicaksono; Yudhiakuari Sincihu; Adi P Hendrata (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2022)
Introduction: Human exposure to microplastics continues to rise. Microplastics are harmful and are suspected of contributing to various health problems in humans, including reduced liver function.Purpose: This study aimed to determine the effect of oral polyvinyl chloride microplastic consumption on alkaline phosphatase (ALP) and gamma-glutamyl transferase (GGT) levels in Rattus norvegicus Wistar strain.Method: Male Rattus norvegicus Wistar strain experiments were separated into control and experimental groups, with the experimental group receiving a 0.5 mg/day dose of polyvinyl chloride microplastic. The experimental animals' blood was taken using the cardiac puncture technique, and the ALP and GGT levels were determined using the kinetic photometric test method.Result and Discussion: The Shapiro-Wilk normality tests showed that the ALP variable from the control group (P=0.342) and the experimental group (P=0.727) was significantly different from the GGT variable from the control group (P=0.482) and experimental group (P=0.099). Thus, the data for the ALP and GGT variables are claimed to be normally distributed. The ALP variable (P = 0.237) and the GGT variable (P = 0.839) both passed the significant homogeneity test, indicating that the ALP and GGT variable data were homogeneous. The independent comparison test T-test findings indicated that the ALP variable (P=0.602) and the GGT variable (P=0.161) were not statistically significant.Conclusion: The oral administration of polyvinyl chloride microplastic had no significant influence on the ALP and GGT levels in the blood of Rattus norvegicus Wistar strain in the experimental group compared to the control group.